The role of majelis taklim darushoffa in educating islamic education for teenagers in Pulo Brayan Urban Village, Medan City - Mulia Sakti; Sakban Lubis; Khoirul Anam (At Turots: Jurnal Pendidikan Islam, 2024)
Adolescence is a transitional phase marked by the need for guidance and direction to understand oneself, often characterized by selfishness and a strong curiosity. Islamic education plays a crucial role in shaping the identity and morals of adolescents, hence Majelis Taklim Darushoffa serves as an Islamic educational institution providing guidance and direction to adolescents in understanding religious values. The research method used is qualitative with descriptive analysis. Informants include leaders, teachers, and active adolescent members involved in Majelis Taklim Darushoffa activities. Primary data is obtained through direct observation and interviews, while secondary data is sourced from journals, articles, and related documentation. Data analysis involves collection, reduction, presentation, and conclusion. The result of this research is the role carried out by majelis taklim in educating Islamic education on adolescents in Pulo Brayan village, Medan city is by utilising social media (Youtube, Facebook and WhatsApp) as a means of da'wah whose main target is teenagers who use social media. The role played by majelis taklim in educating Islamic education on adolescents in the Pulo Brayan sub-district of Medan city is to conduct routine maulid Monday night (Jalsah isnain). Carrying out routine studies on Tuesday afternoons with the subject matter of aqidah, morals and worship. Collaborating with other mosques in Medan City